Use of the Internet for Health Information by the Chronically Ill - Todd H. Wagner; Laurence C. Baker; M. Kate Bundorf; Sara Singer (Centers for Disease Control and Prevention, 2004)
Introduction Chronic conditions are among the leading causes of death and disability in the United States. The Internet is a source of health information and advice for individuals with chronic conditions and shows promise for helping individuals manage their conditions and improve their quality of life. Methods We assessed Internet use for health information by people who had one or more of five common chronic conditions. We conducted a national survey of adults aged 21 and older, then analyzed data from 1980 respondents who had Internet access and who reported that they had hypertension, diabetes, cancer, heart problems, and/or depression. Results Adjusted rates for any Internet use for health information ranged from 33.8% (heart problems only) to 52.0% (diabetes only). A sizable minority of respondents particularly individuals with diabetes reported that the Internet helped them to manage their condition themselves, and 7.9% said information on the Internet led them to seek care from a different doctor. Conclusion Use of the Internet for health information by chronically ill patients is moderate. Self-reported effects on choice of treatment or provider are small but noteworthy.